Peranan Pendidikan Agama Kristen Menangani Masalah Ekologi - Simon Simon (EDULEAD: Journal of Christian Education and Leadership, 2021)
This article reviews how to base Christian Religious Education on ecological problems. This topic is needed to be discussed because Christianity is often seen as not paying attention to ecological problems. Christianity is considered to be more dominant in paying attention to doctrinal than on ecological issues. Christian religious educators as cognitive and moral stewardship of students are expected to contribute to landing PAK (Christian Education) on the ecological problems that occur. The method used in this paper is descriptive qualitative with a literary approach. The description of this article shows how the role of PAK is seen in ecological problems, of course, PAK teachers teach and develop paradigms of ecological problems among students. PAK teachers teach intermittently about ecological issues with full creativity. The PAK teachers themselves became aware of the actual actions being taken. This issue is important to pay attention to or analyze, so that humans have full awareness in maintaining their environment, so as not to leave a damaged natural heritage in the next generation.AbstrakArtikel ini mengulas bagaimana mendaratkan Pendidikan Agama Kristen pada permasalahan ekologi. Topik ini perlu dibahas karena kekristenan sering dianggap tidak peduli pada masalah-masalah ekologi. Kekristenan dianggap lebih dominan memberi perhatian pada pengajaran dokrinal iman dibandingkan mengenai permasalahan ekologi. Pendidik Agama Kristen sebagai penata kognitif dan penata moralitas nara-didik, diharapkan dapat berkontribusi bagaimana mendaratkan PAK pada permasalahan ekologi yang terjadi. Metode yang digunakan pada tulisan ini tentunya deskriftif kualitatif dengan pendekatan literatur. Uraian dari dari artikel ini bagaimana peran PAK terlihat dalam permasalahan ekologi, tentunya pendidik PAK mengajarkan dan membangun paradigma permasalahan ekologi bagi nara-didik. Pengajar PAK mengajarkan secara berkesinam-bungan mengenai permasalahan ekologi dengan penuh kreativitas. Diri pengajar PAK menjadi teladan dengan adanya tindakan yang nyata diperbuat. Masalah ini penting untuk diperhatikan atau ditelaah, supaya manusia memiliki kesadaran yang penuh dalam menjaga lingkungannya, agar tidak meninggalkan warisan alam yang rusak kepada generasi yang akan datang.